Second Account Instagram as Gen Z's Self Identity: A Study of Cultural Phenomenon of Self-Expression - Nugraha, Ika; Sukmarini, Andi Vita; Yusuf, Muhammad (Borong Newinera Publisher, 2023)
This study aims to determine how gen z in Kabupaten Maros uses a second Instagram account as a self-identity in a study of the cultural phenomenon of self-expression. Using a qualitative research method with descriptive analysis. A total of 5 informants interviewed came from gen z in Kabupaten Maros. The results of the study explain that informants have various reasons and goals in using Instagram, as well as how they distinguish between primary and secondary accounts. The majority of informants started using Instagram to stay connected with friends and get the latest information. Instagram functions as a platform for communicating and following social trends. This shows that Instagram is not just social media, but also a tool for building and maintaining social relationships in the digital era. The conclusion of the research results shows that the use of second Instagram accounts among gen Z in Kabupaten Maros functions as a tool to express themselves, maintain privacy, and build more intimate social relationships. This phenomenon reflects changes in the way gen Z builds self-identity and interacts in the digital era, where privacy and freedom of expression are very important. Social and cultural factors that encourage gen z in Kabupaten Maros to create and use second Instagram accounts are peers, freedom of expression, social media culture and the need to maintain privacy.